Parents' experiences of a health dialogue in the child health services: a qualitative study - Linda Håkansson; Mariette Derwig; Ewy Olander (BMC, 2019)
Abstract Background The Child Health Services in Sweden is a well-attended health promoting setting, and thereby has an important role in promoting healthy living habits in families with young children. Due to lack of national recommendations for health dialogues, a Child Centred Health Dialogue (CCHD) model was developed and tested in two Swedish municipalities. The aim of this study was to explore parents' experiences of health dialogues based on the CCHD model focusing on food and eating habits during the scheduled child health visit at four years of age. Methods A qualitative design with purposeful sampling was used. Twelve individual interviews with parents were conducted and analysed with qualitative content analysis. Results The analysis resulted in three categories: The health dialogue provides guidance and understanding; Illustrations promote the health dialogue; and Space for children and parents in the health dialogue. In addition, analysis of the latent content resulted in a single theme reflecting the parents' voice on the importance of having a health dialogue on food and eating habits. The health dialogue, promoted by illustrations, provided guidance and understanding, and gave space for children's and parents' involvement. Conclusions The results indicate that health dialogues using the CCHD- model create supportive conditions for family members' active participation in the visits, which may strengthen empowerment and health literacy. The study provides knowledge and guidance for further development, evaluation and implementation of the model.